Theology in Australia - Peter Howard (St Andrews Encyclopaedia of Theology)
Theology, in Australia’s brief history, has been shaped by its colonial origins, the impact of the changing demographics of the Christian population, and the secular strand in Australian history. This article outlines the historical development of theology in Australia, the institutional frameworks which shaped it, and the contours theological thought has currently assumed. The designation ‘theology’ in what follows refers to Christian theology. The term ‘theology’, as a ‘cluster concept’, includes biblical studies, biblical theology, and other terms that are constitutive of this field of knowledge sometimes referred to as ‘Religious’ or ‘Christian Studies’ or ‘Divinity’. The term ‘Protestant’ is used in the generally understood way to refer to ‘those western European and North American churches which chose to distinguish themselves from Roman Catholicism and maintain their religious independence’ (Sherlock 1993: 476). The first section outlines the development of Christian theology in Australia for the first 150 years after European colonization. This occurred largely in denominational contexts, outside though often associated with universities, and was driven by the need to provide clergy to minister to a diverse, multicultural, immigrant society. The second section addresses a confluence of factors in the ‘long’ 1960s which have contributed to the development of a more confident ‘local’ theological culture. Section three explores the transition from ‘theology produced in Australia’ as an accident of residence to a genuinely ‘Australian theology’ – one that takes account of its historical, social, cultural, and geographic setting. The fourth section explores theologians and currents of theological thought that have emerged since the end of the first decade of the twenty-first century, while the fifth section addresses the prospect of theology in Australia through a brief discussion of graduate theological research and the new priorities shaping theological discussion.